Establishing a measurement array to assess tissue tolerance during loading representative of prosthetic use. (April 2020) - Bramley, J.L.; Worsley, P.R.; Bostan, L.E.; Bader, D.L.; Dickinson, A.S.
Highlights: A protocol was established to investigate tissue response to prosthesis loading. The protocol was evaluated on individuals without amputation, who displayed distinct responses. Ischaemic and inflammatory precursors were observed under low loads in all limbs, including one example residual limb. Results show potential measurements for early detection of skin and sub-dermal damage risk during prosthesis use. Abstract: Background: In the early stages of rehabilitation after primary amputation, residual limb soft tissues have not been mechanically conditioned to support load and are vulnerable to damage from prosthetic use. There is limited quantitative knowledge of skin and soft tissue response to prosthetic loading. Methods: An in-vivo protocol was developed to establish suitable measures to assess tissue tolerance during loading representative of early prosthesis use. Ten participants without amputation one participant with trans-tibial amputation were recruited, and pressure applied to their calf in increments from 20 to 60 mmHg. Measurements were recorded at relevant skin sites including interface pressures, transcutaneous oxygen (TC PO2 ) and carbon dioxide (TC PCO2 ) tensions and inflammatory biomarkers. Findings: At the maximum cuff pressure, mean interface pressures were between 66 and 74 mmHg, associated with decreased TC PO2 values. On the release of pressure, the ischaemic response was reversed. Significant upregulation ( p < 0.05) in inflammatory biomarker IL-1α and its antagonist IL-1RA were observed at all sites immediately following loading. Interpretation: The protocol was successful in applying representative prosthetic loads to lower limb tissues and monitoring the physiological response, both in terms of tissue ischemia and skin inflammation. Results indicated that the measurement approaches were sensitive to changes in interface conditions, offering a promising approach to monitor tissue status for people with amputation.